The journey from an organizational outsider to insider - Onboarding processes at three sites in the global company Aptiv - Darvelid, Julia; Eklund, Nicolina (My University, 2020)
Today’s labour market is more globalized and rapidly changing than ever before. In the engineering area there is a high demand on skilled workers for complex roles which makes it important for companies to attract and retain employees. One big part in making sure that employees stay is an efficient and well-functioning onboarding program. Aptiv is a global company operating in the car industry working on software solutions for autonomous driving, among other things. During the last year a journey towards One Aptiv has begun, where the harmonization of onboarding across the sites is one step. This thesis aims to firstly map the onboarding processes at three Aptiv-sites, in Gothenburg, Krakow and Wuppertal, and secondly to exemplify informal aspects connected to said onboarding. Thirdly the results from these questions are analysed to see how Aptiv facilitates the journey from organizational outsider to insider, from the perspective of the organizers of the onboarding. To fulfill this aim a method divided into two phases was created. In phase 1 the onboarding process at each site was mapped, and this was done through review of site-specific documents and interviews with all responsible parties. In phase 2 the informal structures were examined by six interviews, three with managers and three with mentors. The results in phase 1 show a similar division of responsibilities between the organizers, consisting of human resources, managers, trainers and mentors. However, the execution and content differs, for example regarding role distribution and amount of activities. This was investigated further in phase 2 using the data driven themes of organization, SFO-role and mentorship. All three sites have onboarding processes in place to take care of new employees, but there are gaps where improvement is desirable. Three key areas for improvement were identified: expressing expectations, syncing the onboarding between and within sites, and increasing the support for mentors.
Keywords: Onboarding; organizational socialization; Aptiv; mentorship; communities of practice